2004
DOI: 10.1212/01.wnl.0000147478.03911.28
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of cognitive-motor intervention in MCI and mild to moderate Alzheimer disease

Abstract: A long-term CMI in ChEI-treated early Alzheimer disease patients produced additional mood and cognitive benefits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
200
1
15

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 273 publications
(228 citation statements)
references
References 33 publications
12
200
1
15
Order By: Relevance
“…Given the relative lack of tests and growing importance of such measures, it is clear that the development of ecologically valid tests would benefit rehabilitation research as well as the general field of Neuropsychology. 5,7,15,16,17,18,24,25,27,30,31,33 12 Narrative memory (other) 3,23,28,30 18,23,26,33, 15,21,22,30,31,33 6 Rivermead Behavioural Memory Test (RBMT) 7,8,16,17,26,27,31,33,34 3,7,23,30,31,36 1,3,4,5,15,28,29,32 1 The ...…”
Section: Methodological Challenge 4: Outcome Measuresmentioning
confidence: 99%
“…Given the relative lack of tests and growing importance of such measures, it is clear that the development of ecologically valid tests would benefit rehabilitation research as well as the general field of Neuropsychology. 5,7,15,16,17,18,24,25,27,30,31,33 12 Narrative memory (other) 3,23,28,30 18,23,26,33, 15,21,22,30,31,33 6 Rivermead Behavioural Memory Test (RBMT) 7,8,16,17,26,27,31,33,34 3,7,23,30,31,36 1,3,4,5,15,28,29,32 1 The ...…”
Section: Methodological Challenge 4: Outcome Measuresmentioning
confidence: 99%
“…17 They are also a common reason for institutionalization of people with dementia and they increase the burden and stress of caregivers. 55,57,60 Nonpharmacologic Interventions Nonpharmacologic interventions are recommended as the most appropriate initial strategy for managing inappropriate behaviors in dementia because (1) they address the psychosocial/environmental underlying reason for the behavior, and (2) they avoid the limitations of pharmacologic interventions, namely, adverse side effects, drug-drug interactions, and limited efficacy. 15,17,61 Increased involvement of caregivers often has a secondary benefit of providing overburdened caregivers with an opportunity to receive support, information, and skills.…”
Section: Managing Mood Disorders and Behavior Problemsmentioning
confidence: 99%
“…Olazarán and co-workers [56] only, investigating both AD and MCI patients, found better cognitive outcomes after cognitive stimulations in patients with low, compared with those with high educational level. This surprising result is likely due to the fact that in patients with high CR is needed accumulate more AD neuropathology to show same clinical symptoms of patients with low CR.…”
Section: Discussionmentioning
confidence: 98%
“…This surprising result is likely due to the fact that in patients with high CR is needed accumulate more AD neuropathology to show same clinical symptoms of patients with low CR. The Authors [56] concluded that patients with high CR were less able to learn new generalizable strategies useful to improve cognitive performances. However, further studies assessing relationship between different CR levels and non-pharmacological treatments seem to be necessary and desirable in the immediate future.…”
Section: Discussionmentioning
confidence: 99%